PENGARUH SUHU AKTIVASI CO2 TERHADAP KAPASITANSI SPESIFIK ELEKTRODA KARBON SUPERKAPASITOR DARI TANDAN KOSONG KELAPA SAWIT - Taer, E.; Mustika, W.S.; Taslim, R. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Effect of CO2 activation temperature in production of carbon electrode supercapacitor against specific capacitance has been investigated and analyzed. Carbon electrodes in this study were produced from oil palm empty fruit bunches (EFB) waste derived from people’s plantations. The electrodes production were begun with cutting the cob into small flake of EFB into 5 cm length, followed by a milling process, chemical activation used a 0.3 M KOH, hydraulic pressing and followed by carbonization process at a temperature of 800 oC. The physical activation was carried out at a temperature of 800, 850, and 900 oC in CO2 gas environment. Specific capacitance was determined by cyclic voltammetry method and its found to be as high as 39.77 Fg-1, 65.84 Fg-1, 45.06 Fg-1, 41.30 Fg-1 for activation temperature of 0, 800, 850, and 900 oC, respectively . The results showed that the temperature of 800 oC was the best activation temperature in production of carbon electrodes from EFB. In addition, also calculated physical properties such as mass, thickness, and diameter were measured to determine the density of the electrode. The density of each electrode for temperature activation of 0, 800, 850, and 900 oC were 2.664 g cm-3, 1.891 g cm-3, 2.045 g cm-3, 2.131 g cm-3, respectively. As a complement, the electrode structure has also analyzed by using X-Ray Difraction method. Keywords : activated carbon , oil palm empty fruit bunches , activation of CO2 , supercapacitor.